2013
DOI: 10.1051/parasite/2013019
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors associated with ovine toxoplasmosis in Northeast Brazil

Abstract: Serum samples of 930 sheep were tested by ELISA to assess the prevalence of anti-Toxoplasma gondii antibodies and to identify risk factors associated with the presence of toxoplasmosis in two regions of Rio Grande do Norte (Northeast Brazil), with different climatic conditions. The overall estimated prevalence was 22.1%, with 26.3% and 17.8% positive sheep in Leste Potiguar and Central Potiguar regions, respectively. Among the positive sheep, 18.1% had low-avidity IgG antibodies, suggesting the occurrence of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 28 publications
(35 reference statements)
7
22
3
1
Order By: Relevance
“…The seroprevalence results from the present study are in accordance with other results previously described in Brazil (PEREIRA et al, 2012;ANDRADE et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…The seroprevalence results from the present study are in accordance with other results previously described in Brazil (PEREIRA et al, 2012;ANDRADE et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…The reason for this may be that the most of B. indicus in DU used running water for drinking, as it was easily available. The present results were in accordance to those of Andrade et al (2013), who investigated seroprevalence of toxoplasmosis in O. aires in Brazil and reported a higher infection in O. aries using running water for drinking purposes. Pinheiro et al (2009) also pointed out running water as a risk factor for toxoplasmosis.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, contaminated water led to infection, if used unfiltered (Dubey, 1998). Drinking water must be considered as a source for transmission of T. gondii infection (Andrade et al 2013). During the present research, a higher % of infected B. indicus using running water was recorded.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The first, conducted by Neto et al (2008) in the Eastern Seridó region, found that the seroprevalence for toxoplasmosis was 30.6%. Recently, our group observed seroprevalence of anti-T. gondii antibodies of 22.1% among sheep in the same State, and the age of the animals, presence of cats and use of unexposed water sources were risk factors for toxoplasmosis in sheep (CLEMENTINO ANDRADE et al, 2013). This value is close to those of previous observations in the same state: 29.4% and 20.7% of the sheep tested positive in the municipalities of Lajes and Mossoró, respectively (CLEMENTINO et al, 2007;SOARES et al, 2009).…”
Section: Discussionsupporting
confidence: 82%